(untitled) (Third Sector Social Economic Review, 2017)
The Turkish cooperatives need to grow and diversify to become stronger. While it is possible to achieve growth by increasing the number of cooperatives and increasing the number of members on one side, it is necessary to diversify the growth on the other side, taking into account the developments as well as social needs. Individual budgets, as well as the limited availability of human capital, limit the capability of individual companies to in the range of products they can offer. However, the product range can be increased through cooperatives, in the role of a social communication network. Cooperatives should have awareness for innovation; however, the management of the cooperatives should also have a good understanding of their own performance. In this paper, information will be provided about NAUTILUS, which, as a cooperative, is a good example of a regional social-economic network.